Robust gain-scheduled autopilot design with anti-windup compensation for a guided projectile - Thai, Sovanna; Theodoulis, Spilios; Roos, Clément; Biannic, Jean-Marc (CEAS aeronautical journal, 2023)
This article deals with the control design of a dual-spin projectile concept, characterized by highly nonlinear parameter-dependent and coupled dynamics, and subject to uncertainties and actuator saturations. An open-loop nonlinear model stemming from flight mechanics is first developed. It is subsequently linearized and decomposed into a linear parameter-varying system for the roll channel, and a quasi-linear parameter-varying system for the pitch/yaw channels. The obtained models are then used to design gain-scheduled H ∞ baseline autopilots, which do not take the saturations into account. As a major contribution of this paper, the saturation nonlinearities are addressed in a second step through anti-windup augmentation. Three anti-windup schemes are proposed, which are evaluated and compared through time-domain simulations and integral quadratic constraints analysis. Finally, complete guided flight scenarios involving a wind disturbance, perturbed launch conditions, or aerodynamic uncertainties, are analyzed by means of nonlinear Monte Carlo simulations to evaluate the improvements brought by the proposed anti-windup compensators.